2019
DOI: 10.1371/journal.pone.0215307
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between individual ventilatory threshold and maximal fat oxidation (MFO) over different obesity classes in women

Abstract: Objective The use of the Individual Ventilatory Threshold (IVT), as parameter to prescribe exercise intensity in individuals with obesity, has become more frequent during the last years. This study aimed to evaluate the relationship between IVT and Maximal Fat Oxidation (MFO) in women with obesity. Methods Fifty-two obese female adults (age = 43.6±10.9 years; BMI = 38.5±5.2 kg/m 2 ) were included in this study. According to the BMI classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In contradiction with this paradigm, we observed a positive association between body fatness and the fat oxidation increase in response to physical exercise at FATmax ( Table 2 ). The results of the present study agree with Emerenziani et al, [ 25 ] who observed a higher MFO in women with class III obesity compared with class I and II individuals, and supports previous studies reporting a higher MFO [ 26 ] and TFO [ 27 , 28 ] in subjects with obesity when compared against lean counterparts, as well as a lower RER peak during moderate-intensity exercise [ 27 ]. Rationale for a positive association between body fatness and exercise fat oxidation are: (I) increased free fatty acid circulating levels and (II) augmented intramuscular triglyceride oxidation [ 6 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contradiction with this paradigm, we observed a positive association between body fatness and the fat oxidation increase in response to physical exercise at FATmax ( Table 2 ). The results of the present study agree with Emerenziani et al, [ 25 ] who observed a higher MFO in women with class III obesity compared with class I and II individuals, and supports previous studies reporting a higher MFO [ 26 ] and TFO [ 27 , 28 ] in subjects with obesity when compared against lean counterparts, as well as a lower RER peak during moderate-intensity exercise [ 27 ]. Rationale for a positive association between body fatness and exercise fat oxidation are: (I) increased free fatty acid circulating levels and (II) augmented intramuscular triglyceride oxidation [ 6 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…As the participants were sedentary and overweight with a low aerobic capacity (19,42), the discontinuation of lipid oxidation with constant low-intensity exercise may be attributed to their metabolic inflexibility. In this context, as an alternative method, the use of the individual ventilatory threshold can be a useful parameter that identifies physical activity that maximizes fat oxidation in obese individuals (14).…”
Section: Discussionmentioning
confidence: 99%
“…For most individuals with type 2 diabetes engaging in a walking-based exercise training, the sustainable intensity between 40 and 59% heart rate reserve (HRR, calculated as a percentage of maximum heart rate minus resting heart rate), corresponding to a rating of perceived exertion (RPE) of 11e13 on a 6e20 scale [89] (Table 3) should be encouraged, even if lower intensities should be initially prescribed for very deconditioned patients. Unfortunately, exercise intensity is rarely prescribed on an individual basis, although some studies have recently argued for the use of tailored approaches, with particular emphasis on the individual ventilatory threshold [90,91], in order to improve cardiorespiratory fitness and promote weight loss and maintenance. Further studies are still required to confirm that the individual ventilatory threshold may be an appropriate guide in prescribing exercise intensity in these patients.…”
Section: Walking Prescriptionmentioning
confidence: 99%